Hospital Admission in the Latent versus the Active Phase of Labor: Comparison of Perinatal Outcomes - Viola Seravalli; Noemi Strambi; Enrica Castellana; Maria Alessia Salamina; Chiara Bettini; Mariarosaria Di Tommaso (MDPI AG, 2022)
Background: Admission in the latent phase of labor has been associated with increased risk of obstetric interventions compared to admission in the active phase. We aimed to investigate the relationship between labor phase at admission and obstetric and neonatal outcomes. Methods: A retrospective cohort study was conducted on 1005 women with uncomplicated singleton pregnancy admitted for spontaneous labor. Cesarean section rate and other perinatal outcomes were compared between women admitted in the latent phase and those admitted in the active phase. Results: Admission occurred in the active phase of labor for 331 women (32.9%) and in the latent phase for 674 (67.1%). Admission in the latent phase was more frequent in nulliparous than in multiparous (p < 0.01) and for Italian patients compared to foreigners. The incidence of caesarean section was similar between groups. Admission in the latent phase increased the likelihood of epidural analgesia (OR 3.47, 95% CI 1.96-6.14, in nulliparous, and OR 2.58, 95% CI 1.37-4.84, in multiparous) and increased the rate of augmentation of labor with oxytocin in multiparous (OR 2.87, 95% CI 1.05-7.85), without difference in neonatal outcomes. Conclusions: Admission in the latent phase is associated with more frequent use of epidural analgesia, without an increase in cesarean section or adverse neonatal outcomes.